Pertanggung Jawaban Pidana Terhadap Pemerkosa Anak Kandung - Ridwan, Muhammad Basitur; Hapsari, Ifahda Pratama (Fakultas Syariah INSURI Ponorogo, 2023)
The kid is a gift of God Almighty, we must safeguard and care for him since every child has the right to survive. The rising number of occurrences of adult sexual abuse of kids both at school and in public settings implies a lack of child protection, as well as having a directly recognized physical and psychological effect by children as victims of sexual abuse. Sexual abuse of kids must be resisted with solid action and halted as soon as feasible. Prevention may be done via sex education, not just by parents but also by other parties, including schools. Child protection measures must begin as early as possible, so that children may engage ideally in the growth of the country and state, since everyone who performs their acts must be accountable and punished according to their actions.